Identification of Cognitive Activities That Underlie Variations in Lecture Note-Taking: An Exploration of Japanese and Chinese High School Students’ Strategies in Mathematics Class - Liu, Mengsi; Uesaka, Yuri (Frontiers in Education, 2022)
Lecture note-taking has been proven beneficial for learning at different educational levels. Previous studies have largely focused on the relationship between the outcomes of note-taking on a blank paper (e.g., measurements of the quantity and/or quality of notes taken) and student learning performance. However, there is no consensus as to what makes good notes. It is difficult to judge whether lecture note-taking is effective based only on the measurements of the notes. Past explorations have not adequately considered the cognitive activities that accompany such a process. Thus, using the interview method, the present study aimed to identify how lecture note-taking is used as a cognitive activity, and what factors influence it. To increase the possible range of note-taking approaches that could be observed, data from different cultural environments in Japan and China were sampled. Semi-structured interviews were conducted with 20 high school students from both countries (10 in each) to explore the cognitive activities in which students engage when taking lecture notes in mathematics class. Based on learning strategy models and studies, as well as using a thematic analysis, a new hierarchical framework of lecture note-taking, comprising shallow and deep lecture note-taking, was proposed. Deep lecture note-taking uses cognitive, metacognitive, and resource management functions. Furthermore, a comparison of students from the two countries revealed that their beliefs and teachers’ instructions were potential factors influencing their lecture note-taking. Utilizing interview as the research method allowed us to obtain new insights into the cognitive activities that accompany lecture note-taking, such as the metacognitive function, which has rarely been explored in previous research. Future work is expected to commence on new measures based on this theoretical framework that gauges the cognitive activity of lecture note-taking. This study also calls for the exploration of effective note-taking instruction that considers the cognitive activity of note-taking.